Migraine Patients With Cardiovascular Disease and Contraindications: An Analysis of Real-World Claims Data - David W. Dodick; Anand S. Shewale; Richard B. Lipton; Seth J. Baum; Steven C. Marcus; Stephen D. Silberstein; Jelena M. Pavlovic; Nathan L. Bennett; William B. Young; Hema N. Viswanathan; Jalpa A. Doshi; Howard Weintraub (SAGE Publishing, 2020)
Introduction: Triptans, the most commonly prescribed acute treatments for migraine attacks are, per FDA labeling, contraindicated in cardiovascular (CV) disease patients and have warnings and precautions for those with CV risk factors. Methods: Headache specialists, cardiologists, and health economics and outcomes researchers convened to identify diagnostic codes for: (1) CV diseases contraindicating triptans based on FDA labeling; (2) conditions comprising "other significant underlying CV disease"; and (3) CV risk factors included as warnings and precautions for triptans. A retrospective, cross-sectional analysis of commercially insured adult US migraine patients in the 2017 Optum ® Clinformatics ® Data Mart (CDM) and the 2017 IBM ® Watson Health MarketScan ® Commercial Claims database was used to estimate the proportion of migraine patients with CV contraindications and warnings and precautions to triptans. Results: Of the 56,662 migraine patients analyzed from Optum CDM, 13.5% had ≥1 CV disease as specified in triptan labeling and an additional 8.5% had ≥1 "other CV disease" judged by the panel to constitute a "significant underlying CV disease" (total: 22.0% migraine patients). Of 176 724 migraine patients analyzed from MarketScan, 12.2% had ≥1 CV disease as specified in the labeling and an additional 8.0% had ≥1 "other significant underlying CV disease" (total: 20.2% of migraine patients). An additional 25.4% and 25.1% of migraine patients had ≥2 CV risk factors in Optum CDM and MarketScan. In total, 47.4% and 45.3% of migraine patients in both databases had a CV disease specified as a contraindication, an "other CV disease" endorsed as significant, or ≥2 CV risk factors identified as warnings and precautions to triptans. Conclusions: Analyses of more than 230,000 people with migraine showed that ≥20% of commercially insured US migraine patients have a CV condition that specifically contraindicates triptan treatment, and an additional 25% have ≥2 CV risk factors identified as warnings and precautions to triptans.